The Application Of Library 2.0 Concept For Enhancing The Library OPAC - Salleh Hudin, Mustaffa (2008)
OPAC is the conventional library service that only allows for one-way flow of information. This project presents an overview of Web 2.0 and Library 2.0 including its definition, technologies involved and sites currently advocated as examples of Web 2.0. Library 2.0 gives library users the power to share their experiences. Library 2.0 can be summarized as being user-driven that enables attracting users to enrich information resources. Library 2.0 concepts can be implemented to enhance OPAC and increase users' satisfaction especially for new generation. Enhanced OPAC involved the implementation of new function for search engine, the advancement in exchanging data with other application and services, additional content which is used to describe the materials in library collections, capability to utilize external content services, and the application of Web 2.0 tools. Users are able to get more descriptions about items in a library collection and will be able to contribute their opinions about the library collection in the future. Pilot survey shows that UUM Librarians are very satisfied with the concept of Enhanced OPAC and are willing to use it in the future.